Opening of Astrocytic Mitochondrial ATP-Sensitive Potassium Channels Upregulates Electrical Coupling between Hippocampal Astrocytes in Rat Brain Slices - Wang, Jiangping (Public Library of Science, 2013)
Astrocytes form extensive intercellular networks through gap junctions to support both biochemical and electrical coupling between adjacent cells. ATP-sensitive K(+) (K(ATP)) channels couple cell metabolic state to membrane excitability and are enriched in glial cells. Activation of astrocytic mitochondrial K(ATP) (mitoK(ATP)) channel regulates certain astrocytic functions. However, less is known about its impact on electrical coupling between directly coupled astrocytes ex vivo. By using dual patch clamp recording, we found that activation of mitoK(ATP) channel increased the electrical coupling ratio in brain slices. The electrical coupling ratio started to increase 3 min after exposure to Diazoxide, a mitoK(ATP) channel activator, peaked at 5 min, and maintained its level with little adaptation until the end of the 10-min treatment. Blocking the mitoK(ATP) channel with 5-hydroxydecanoate, inhibited electrical coupling immediately, and by 10-min, the ratio dropped by 71% of the initial level. Activation of mitoK(ATP) channel also decreased the latency time of the transjunctional currents by 50%. The increase in the coupling ratio resulting from the activation of the mitoK(ATP) channel in a single astrocyte was further potentiated by the concurrent inhibiting of the channel on the recipient astrocyte. Furthermore, Meclofenamic acid, a gap-junction inhibitor which completely blocked the tracer coupling, hardly reversed the impact of mitoK(ATP) channel's activation on electrical coupling (by 7%). The level of mitochondrial Connexin43, a gap junctional subunit, significantly increased by 70% in astrocytes after 10-min Diazoxide treatment. Phospho-ERK signals were detected in Connexin43 immunoprecipitates in the Diazoxide-treated astrocytes, but not untreated control samples. Finally, inhibiting ERK could attenuate the effects of Diazoxide on electrical coupling by 61%. These findings demonstrate that activation of astrocytic mitoK(ATP) channel upregulates electrical coupling between hippocampal astrocytes ex vivo. In addition, this effect is mainly via up-regulation of the Connexin43-constituted gap junction coupling by an ERK-dependent mechanism in the mitochondria.